Clero criminale: L'onore della Chiesa e i delitti degli ecclesiastici nell'Italia della Controriforma. Volume 1. I documenti: il Cinquecento Criminal Clergy: The Honor of the Church and Crimes of Priests in Counter-Reformation Italy. Volume 1, Documents: the Sixteenth Century - Giovanni Romeo (Fuori Collana, 2014)
With this rich anthology of sources, most of which are made available here for the first time, Michele Mancino and Giovanni Romeo add another element to the research project that began with their recent book (Clero criminale. L'onore della Chiesa e i delitti degli ecclesiastici nell'Italia della Controriforma, Laterza, Roma-Bari, 2013, 4th ed.). The two parts document from a range of perspectives the way in which the Tridentine project of combating the common crimes of the clergy was undone before the end of the sixteenth century. Instead, the Roman curia was mainly concerned with enforcing the right of delinquent priests to be judged only by ecclesiastical tribunals, a strategy intended to defend the honor of the clergy that was followed persistently over the long term. The material presented here describes a previously unknown historical precedent for the recent revelations about the treatment of pedophile priests.